Conflict and critical theories - Gehring, Krista S. (CrimComics, 2023)
"CrimComics offers a new way to approach criminological theory by engaging students with impactful, highly visual illustrated texts. Each Crimcomics Issue traces the development of the theory--placing it in social and political context-- and demonstrates its application to the real world. The last page of each Issue features review questions and key terms"--